2022
DOI: 10.3390/s22155783
|View full text |Cite
|
Sign up to set email alerts
|

Planar Junctionless Field-Effect Transistor for Detecting Biomolecular Interactions

Abstract: Label-free field-effect transistor-based immunosensors are promising candidates for proteomics and peptidomics-based diagnostics and therapeutics due to their high multiplexing capability, fast response time, and ability to increase the sensor sensitivity due to the short length of peptides. In this work, planar junctionless field-effect transistor sensors (FETs) were fabricated and characterized for pH sensing. The device with SiO2 gate oxide has shown voltage sensitivity of 41.8 ± 1.4, 39.9 ± 1.4, 39.0 ± 1.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…For peptide synthesis, however, conditions are more demanding than for nucleotide synthesis, i.e., acidic conditions required for stepwise deprotection cycles are more extreme, and possible side reactions of amino acid side chains must be averted. We recently described an improved reactor concept for electrochemical acid production, and demonstrated that it affords good yields in the local deprotection of acid-labile groups in organic electrolytes compatible with peptide synthesis [12,13]. To achieve high density microarrays, these electrochemical reactors can be miniaturized and integrated with MOS circuits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For peptide synthesis, however, conditions are more demanding than for nucleotide synthesis, i.e., acidic conditions required for stepwise deprotection cycles are more extreme, and possible side reactions of amino acid side chains must be averted. We recently described an improved reactor concept for electrochemical acid production, and demonstrated that it affords good yields in the local deprotection of acid-labile groups in organic electrolytes compatible with peptide synthesis [12,13]. To achieve high density microarrays, these electrochemical reactors can be miniaturized and integrated with MOS circuits.…”
Section: Introductionmentioning
confidence: 99%
“…In tune with this innovation, we have revisited peptide synthesis protocols relying on acid-labile protection schemes, to evaluate the feasibility of obtaining high purity peptides via in-situ synthesis on semiconductor oxide surfaces similar to those used in our FET biosensors [13]. Our goal was to validate a suitable surface capable of simulating the chemical conditions of semiconductors or metal oxides which form the interface of today's commercial FETs.…”
Section: Introductionmentioning
confidence: 99%
“…In tune with this innovation, we have revisited peptide synthesis protocols relying on acid-labile protection schemes, to evaluate the feasibility of obtaining high purity peptides via in situ synthesis on semiconductor oxide surfaces similar to those used in our FET biosensors [16,17]. Our goal was to validate a suitable surface capable of simulating the chemical conditions of semiconductors or metal oxides which form the interface of today's commercial FETs.…”
Section: Introductionmentioning
confidence: 99%